T2*-weighted imaging for detection of intracranial silicone oil in MRI obtained with motion correction sequences - Ryuta Yasuda; Masayuki Maeda; Kenichi Takada; Katsuhiro Inoue; Masataka Sugao; Hidenori Suzuki (Egyptian Journal of Neurosurgery)
Abstract Background For magnetic resonance imaging (MRI) findings of intracranial silicone oil migration, little has been described about images obtained with motion correction sequences such as MultiVane XD (Philips Healthcare) that provides high resolution diagnostic images even with severe patient motion. We report a case with intracranial silicone oil migration in which MRI was obtained with MultiVane XD and T2*-weighted imaging (T2*WI) was found the most useful in detecting intracranial silicone oil. Case presentation A 77-year-old female with a history of eye surgery using silicone oil referred to our hospital due to conscious disturbance. Head computed tomography demonstrated multiple intracranial masses whose signal density was similar to that in the operated eyeball and the tentative diagnosis of intracranial silicone oil migration was made. MRI was performed with MultiVane XD due to the significant patient’s restlessness, and among all sequences including T1-weighted imaging (T1WI), T2-weighted imaging (T2WI), fluid-attenuated inversion recovery (FLAIR) and T2*WI, only T2*WI detected intracranial silicone oil. In contrast, another MRI obtained previously with conventional turbo spin-echo detected intracranial silicone oil not only in T2*WI but also in T1WI, T2WI and FLAIR. Phantom experiment revealed that chemical shift artifact played an important role in discriminating silicone oil from artificial cerebrospinal fluid, which attenuated in MultiVane XD. However, T2*WI still showed good discrimination of silicone oil even using MultiVane XD because of susceptibility artifacts. Conclusion T2*WI was the best sequence to detect intracranial silicone oil in MRI obtained with motion correction sequences because of its ability to depict the susceptibility artifacts.